2008
DOI: 10.1093/oxrep/grn009
|View full text |Cite
|
Sign up to set email alerts
|

House prices, money, credit, and the macroeconomy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
390
0
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(438 citation statements)
references
References 33 publications
28
390
0
20
Order By: Relevance
“…In the traditional approach, according to Goodhart and Hofmann (2008), the conections between cross-sections are neglected. The approach of Canova and Ciccarelli (2006) uses the VAR reparametrization to include the cross-sections linkages.…”
Section: Methods Data and Variablesmentioning
confidence: 99%
“…In the traditional approach, according to Goodhart and Hofmann (2008), the conections between cross-sections are neglected. The approach of Canova and Ciccarelli (2006) uses the VAR reparametrization to include the cross-sections linkages.…”
Section: Methods Data and Variablesmentioning
confidence: 99%
“…Besides this, there exists a couple of other studies that have looked into the effect of real house prices on per capita economic growth at the provincial-level in South Africa using 1 See for instance, Leamer (2007), Fisher (2007), (Silos, 2007), Goodhart and Hofmann (2008), , Álvarez et al, (2010), Bulligan (2010), Bandt et al, (2010), Ferrara and Koopman (2010), , Ferrara and Vigna (2010), Ghent and Owyang (2010), Iacoviello (2010), Iacoviello and Neri (2010), Iacoviello and Pavan (forthcoming), Kiyotaki et al, (2011), Cinquegrana (2012, Kydland et al, (2012),. Note, however, there also exists a few studies, such as: Benhabib et al (1991), Greenwood and Hercowitz (1991), McGrattan, et al, (1997), Gomme et al (2001), Davis and Heathcote (2005), Iacoviello (2002Iacoviello ( , 2005 which had also emphasized the role of housing on business cycle way before the recent financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…The striking role played by housing markets in the recent financial crisis has demonstrated that shocks in the housing sector can exert huge effects on real economic activity, in particular through their impact on private consumption and residential investment (Goodhart and Hofmann (2008)). Housing loans constitute the largest liability of households and account for a large proportion of bank lending.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects on housing wealth are not obvious. A permanent increase in house prices could have a positive effect for homeowners, but there is also a negative effect on tenants who have to pay higher rents, and on prospective first-time buyers who have to save more for their intended house purchase, see Poterba (2000) and Goodhart and Hofmann (2008). In addition, increases in the value of owner-occupied housing do not foster the ability of a household to consume more of other goods and services unless that household is willing to realize the increased value, for example, by moving into a less expensive flat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation